Practical grammar of modern Chinese. III, Sentence constituents - Liu, Yuehua, 1937-; Wenyu, Pan; Wei, Gu (Abingdon : Routledge, 2021)
Chinese grammar is characterized by its simple structure, lack of inflections, and wide use of monosyllabic morphemes. With the increased popularity of learning Chinese as a second language, there is a demand for a guide to Chinese grammar that's targeted at second language learners. This four-volume set is one of the earliest and most influential works of Chinese grammar, with a special focus on teaching and learning Chinese as a second language. Drawing on rich teaching experience, the authors analyze a myriad of real world examples to describe Chinese grammatical phenomena and rules while introducing the general grammar system of Chinese. This volume introduces sentence constituents in modern Chinese grammar, including subjects, objects, attributes, adverbials, complements, double references, and parentheses. Since the first edition came out in 1983, this set has been revised twice and remained one of the best sellers in the field. Practitioners and scholars of teaching Chinese as a second language, as well as students with a basic knowledge of Chinese, will find it to be a handy reference.
1 Subject and Object. 2 Object. 3 Attribute. 4 Adverbial. 5 Complement. 6 Double Reference and Parenthesis
OCLC-licensed vendor bibliographic record.
Keywords: Chinese language -- Grammar